AN ANALYSIS OF FIGURATIVE LANGUAGE IN SUMBAWA SONGS - SARTIKA SARTIKA; DEVI HARIANTI (GANEC SWARA, 2024)
This study aims to determine the types  of figurative language contained in Sumbawa songs. To determine the type of figurative language, the researcher uses Keraf's theory.   The method used in this study is a qualitative descriptive method. There are four ways to collect data, namely video observation, documentation, interviews and recordings. Data were analyzed using data reduction, data display and drawing conclusions/verification. The study found five types of figurative language contained  in Sumbawa Songs such as simile, repetition, hyperbole, synecdoche, and personification.